PENGARUH PUPUK ORGANIK DAN BATUAN FOSFAT ALAM PADA INCEPTISOL SEBAGAI MEDIA TANAM TERHADAP PERBANYAKAN MIKORIZA ARBUSKULA (MA) DENGAN BERBAGAI TANAMAN INANG - Budi Prasetya; Ikhya Ulum Ukhtansyah (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
The distribution of very abundant AM in UB forest is very potential to be used as biological fertilizer. Biofertilizer production through the utilization of AM spores requires the multiplication of AM by using host plants namely maize (Zea mays L.), soybean (Glycine max (L) Merill) and tithonia (Tithonia diversifolia) and planting media consisting of soil added with cattle manure and rock phosphate. This study aimed to obtain the best host plants and growing media in producing the number of AM spores and AM colonies so that they can be used as AM biological fertilizer production. The study design used was a factorial randomized group design with host plants (H) as the first factor and planting media (M) as the second factor consisting of 18 treatments with 3 replications. The multiplication results showed that media with an M5 dose (150 kg ha-1 rock phosphate + 5 t ha-1 cattle manure) was high in producing AM spores amounting to 324,67 AM 100 g soil-1 in maize and 61.11% AM colonies in soybeans. Rock phosphate and cattle manure were sources of P in the growing media and AM which was multiplied to carry out its activities in producing phosphatase enzymes to produce P available for plants. Maize and soybeans had stable growth, good rooting, fast plant growth and low root lignin content which made it easy for AM to make colonies.